2009
DOI: 10.1227/01.neu.0000351771.46273.22
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Cyst Formation After Gamma Knife Radiosurgery for Brain Metastases

Abstract: Although DCF is not a widely recognized complication of GKRS for METs, we advocate careful follow-up, with surgical intervention for DCF if necessary, for frequently irradiated and long-surviving patients with METs treated with GKRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
(28 reference statements)
0
19
0
Order By: Relevance
“…In comments on our previous publication focusing on delayed cyst formation in patients with BM surviving > 3 years after SRS, Regis stated that the mean GI value in our series was quite poor (approximately 4) and noted that cyst formation might partially account for this result. 4,13 However, we have long wondered whether either CI or GI truly impacts treatment results, despite these indexes being theoretically regarded as correlating with post-SRS outcomes. We reported that, based on 207 patients with vestibular schwannomas who were followed up for at least 10 years after SRS, CI did not correlate with good tumor control and GI had no impact on the degree of hearing preservation.…”
Section: Discussionmentioning
confidence: 99%
“…In comments on our previous publication focusing on delayed cyst formation in patients with BM surviving > 3 years after SRS, Regis stated that the mean GI value in our series was quite poor (approximately 4) and noted that cyst formation might partially account for this result. 4,13 However, we have long wondered whether either CI or GI truly impacts treatment results, despite these indexes being theoretically regarded as correlating with post-SRS outcomes. We reported that, based on 207 patients with vestibular schwannomas who were followed up for at least 10 years after SRS, CI did not correlate with good tumor control and GI had no impact on the degree of hearing preservation.…”
Section: Discussionmentioning
confidence: 99%
“…The number of reports on CCF cases from various types of primary pathology have been increasing, whilst the aetiopathogenesis of CCF remains to be elucidated. 9,10 Repetitive haemorrhage from an abnormal angiomatous lesion located within or underlying the cyst wall was suggested as a plausible mechanism for cyst enlargement in AVM cases. 9 The CCF in the present cases appeared more than 2-7 years after SRT, and are plausibly derived from a part or the entirety of pre-existing parenchymal injury rather than degenerative change of the necrotic tumour.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Brain radiation necrosis is one of the important untoward sequelae after radiotherapy, including SRT for HNM, especially nasopharyngeal carcinoma (NPC), with imaging findings being characterized by central loss of enhancement surrounded by feathery or reticular enhancement associated with perilesional oedema. [4][5][6][7] Cerebral cyst formation (CCF) is an unusual subset of radiation-induced brain injury and is usually encountered in cases harbouring intracranial disorders embedded in the parenchyma, such as arteriovenous malformation (AVM) 8,9 or brain metastases, 10,11 and rarely extra-axial tumours, such as meningioma 12 and neuroma, 13 treated with stereotactic radiosurgery (SRS). CCF might also occur as a rare consequence of brain injury following definitive radiotherapy for NPC.…”
mentioning
confidence: 99%
“…Late-onset complications after stereotactic irradiation include radiation-induced edema, radiation necrosis, cyst formation, radiation-related tumorigenesis, and radiation-induced cerebrovascular injury. 2,4,8,16,18,25,29,30) We describe a rarely predictable delayed complication which occurred after SRS in a patient with VS.…”
Section: Introductionmentioning
confidence: 93%